Problem Based Learning Model For Mathematics Ability: How Effective Is It? - Darwis, Rahma Hidayati; Patimbangi, Andi (International Journal of Psychosocial Rehabilitation, 2020)
This study aims at determining the effectiveness of problem-based learning models on mathematical abilities (reasoning and communication, connections and problem-solving) of students. This type of research is pre-experimental research since not all variables that affect mathematical ability are controlled. The main variables investigated in this study are mathematical abilities which include: (1) reasoning and communication skills, (2) connections and (3) problem-solving. In addition to these main variables, students and teachers' activity variables were investigated in the problem-based learning process. From the results of the study, it is concluded that the application of problem-based learning models is quite useful used in the learning process, especially in improving the mathematical abilities of students. In addition, the students’ stages of thinking also significantly affect the effectiveness of the use of problem-based learning models. Students who are already at the stage of hypothetical deductive thinking are in accordance with the character of the problem-based learning model.